Rapid diagnosis of egg allergy by targeting ovalbumin specific IgE and IgG4 in serum on a disposable electrochemical immunoplatform. Issue 1 (23rd December 2021) - Gordón Pidal, José M.; Valverde, Alejandro; Benedé, Sara; Molina, Elena; Moreno-Guzmán, María; López, Miguel Ángel; Pingarrón, José M.; Escarpa, Alberto; Campuzano, Susana
Abstract : First electrochemical bioplatforms described for the single and simultaneous determination of two immunoglobulin (Ig) subtypes, IgE and IgG4 specific to ovalbumin (OVA), considered as reliable markers for the diagnosis and monitoring of egg allergy. Abstract : This work reports the first electrochemical bioplatforms described to date for the single and simultaneous determination of two immunoglobulin (Ig) subtypes, IgE and IgG4, considered as reliable markers for the diagnosis and attenuation of food allergy specific to ovalbumin (OVA), one of the major egg allergenic proteins. The bioplatforms are based on the use of commercial magnetic microbeads (MBs) modified with OVA (OVA-MBs) for the selective capture of target Igs and the specific detection of IgE and IgG4 by enzymatic labelling with selective secondary antibodies conjugated to the horseradish peroxidase (HRP) enzyme. Amperometric transduction is carried out on single or dual screen-printed carbon electrodes, SP(d)CEs, in the presence of the H2 O2 /hydroquinone (HQ) system. The developed bioplatforms provide outstanding analytical and operational characteristics in terms of sensitivity (LOD values of 0.003 kU L −1 and 0.0002 μg L −1 for IgE and IgG4, respectively), simplicity and assay time. They were used for the determination of both Igs in serum of patients diagnosed with egg allergy upon a simple dilution (50-and 1000-times for IgE and IgG4 determination, respectively).